The Mountain of Adventure - Blyton, Enid (London Pan Books, 1988)
A mad genius plot, this one, with the children staying in a Welsh farmhouse and discovering peculiar happenings up at the local mountain. Strange noises rumble from it, wolves roam the slopes and crimson smoke issues from the top